Optic Disc Pit with An Atypical Presentation - Neha Arora; Aniket Patel (Delhi Journal of Ophthalmology)
Optic Disc Pit (ODP) results from an imperfect closure of the superior edge of the embryonic fissure, usually associated with macular serous detachment. In our case report, we are presenting optic disc pit with a multilayered separation involving the nerve fibre layer and the outer plexiform layer along with neurosensory detachment.